Dynamics of Microbial Community Structure and Ecological Functions in Estuarine Intertidal Sediments - Yi, Jun; Lo, Linus Shing Him; Cheng, Jinping (Frontiers in Marine Science, 2020)
Microbial communities are important indicators of aquatic ecosystem health, responsible for functional roles sustaining the ecosystem such as nutrient cycling, as well as environmental problems. Urbanized estuaries are vulnerable intersections between terrestrial and marine ecosystems and are susceptible to pressure and perturbation from both natural processes and human activities over time. The response by microbial communities towards changes in the environment should be closely monitored and studied. In this study, microbial communities in brackish intertidal sediments, sampled seasonally over a year along the coast of Yangtze River estuary, were analyzed using 16S rRNA gene sequencing. Potential compositional and functional changes in microbial communities resulting from temporal variation and associated physiochemical gradients in the environment were studied and notable patterns were observed over time. Summer season was recorded with the lowest microbial community α-diversity. For β-diversity, spatiotemporal differentiation in community structures was recorded with seasonal clustering. Proteobacteria was recorded as the most dominant phylum among all sampling sites throughout the year but its relative abundance showed no temporal changes. Instead, relative abundances of phyla Actinobacteria, Chloroflexi, and Verrucumicrobia were found to differ significantly over time, generally favoring the wet Spring and Summer. In contrast, temporal variation was observed for the class Deltaproteobacteria and some of the corresponding sulfate/sulfur-reducing bacterial genera, favoring the dry Autumn and Winter. However, there were no major temporal changes in ecological functions contributed by microbial communities throughout the study period. While results from redundancy analysis showed that the subtle changes in pH in the environment had the greatest impact on microbial community composition, the variation it explained remained relatively low. Alternatively, precipitation, distinguishing the dry and wet seasons of the subtropical monsoon climate zone, was suggested to be another potential key factor influencing microbial community composition and their relative abundances. The present study provides new data and insights on the impact of temporal variation on microbial community composition and ecological function in an urbanized estuarine ecosystem.